2017
DOI: 10.1080/00224499.2017.1280121
|View full text |Cite
|
Sign up to set email alerts
|

Safer Sex in Later Life: Qualitative Interviews With Older Australians on Their Understandings and Practices of Safer Sex

Abstract: Rates of sexually transmitted infections (STIs) are increasing in older cohorts in Western countries such as Australia, the U.K. and the U.S., suggesting a need to examine the safer sex knowledge and practices of older people. This article presents findings from 53 qualitative interviews from the study "Sex, Age & Me: a National Study of Sex and Relationships Among Australians aged 60+." Participants were recruited through an online national survey.We consider how participants understood "safer sex," the impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 61 publications
(105 reference statements)
0
29
0
1
Order By: Relevance
“…A number of studies have highlighted the importance of emotional intimacy for aging individuals' sexuality (Laumann et al 2006;Sandberg 2013;Müller et al 2014;Fileborn et al 2017). In a longitudinal population-based study of aging German men and women, participants in the highest age group (74 years), prioritized "affection" over sexual activity.…”
Section: Emotional Intimacy and Sexuality In Aging Men And Womenmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have highlighted the importance of emotional intimacy for aging individuals' sexuality (Laumann et al 2006;Sandberg 2013;Müller et al 2014;Fileborn et al 2017). In a longitudinal population-based study of aging German men and women, participants in the highest age group (74 years), prioritized "affection" over sexual activity.…”
Section: Emotional Intimacy and Sexuality In Aging Men And Womenmentioning
confidence: 99%
“…In a longitudinal population-based study of aging German men and women, participants in the highest age group (74 years), prioritized "affection" over sexual activity. In the Australian Sex, Age, and Me study (Fileborn et al 2017), qualitative interviews with individuals aged 60 and older revealed that both men and women considered intimacy and bonding a central component of their sexual lives.…”
Section: Emotional Intimacy and Sexuality In Aging Men And Womenmentioning
confidence: 99%
See 1 more Smart Citation
“…Such work could be supported by, for example, ensuring that older Australians are explicitly addressed in sexual health policy, and we reiterate recent calls for such action here . Some participants in our study viewed sexual health as irrelevant to them, even if they were in relatively ‘high‐risk’ relationships , and this likely acts as a significant barrier to discussing sex with their HCP.…”
Section: Discussionmentioning
confidence: 65%
“…This suggests there may be gendered barriers to discussing sex with a HCP, and this warrants further examination, particularly to determine the implications this presents for sexual health campaigns and HCP education. For example, some female participants reported receiving stigmatising responses from male sexual partners in attempting to discuss safer sex practices with them . It is unclear whether or to what extent such highly gendered experiences may in turn shape older women's willingness to discuss sex with HCPs, although several women discussed stigma and embarrassment as a barrier which suggests there may be a connection here; that is, older women's reluctance to discuss sex with HCPs may be situated within broader social norms and attitudes towards older women's sexuality, and stereotypical assumptions about who is ‘likely’ to contract an STI.…”
Section: Discussionmentioning
confidence: 99%